2013
DOI: 10.1210/me.2013-1110
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of JAK2 in Adipocytes Impairs Lipolysis and Improves Fatty Liver in Mice With Elevated GH

Abstract: Nonalcoholic fatty liver disease (NAFLD) is considered the hepatic expression of the metabolic syndrome, and its prevalence is increasing. The factors that influence the development of fatty liver and its progression to steatohepatitis and cirrhosis are not well understood. The pleiotropic hormone, GH, has been associated with an increased risk of NAFLD in humans and mice. GH is known to have diverse effects on lipid metabolism including decreasing body fat in vivo, presumably through stimulation of lipolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 31 publications
8
70
1
Order By: Relevance
“…Of note, A-Jak2 KO mice were obese even when maintained at 20°C. This difference compared with Ucp1 −/− mice may be attributable to the suppression of lipolysis in white adipose tissue as a result of JAK2 deficiency, as we and others have previously shown [25,36]. In this work, we showed that JAK2 is required for full activation of the thermogenic response to a β 3 -adrenergic agonist, suggesting that JAK2 acts downstream of β-adrenergic signalling in adipocytes.…”
Section: Discussionsupporting
confidence: 49%
“…Of note, A-Jak2 KO mice were obese even when maintained at 20°C. This difference compared with Ucp1 −/− mice may be attributable to the suppression of lipolysis in white adipose tissue as a result of JAK2 deficiency, as we and others have previously shown [25,36]. In this work, we showed that JAK2 is required for full activation of the thermogenic response to a β 3 -adrenergic agonist, suggesting that JAK2 acts downstream of β-adrenergic signalling in adipocytes.…”
Section: Discussionsupporting
confidence: 49%
“…Adipocytes were found to be smaller in the SIGFRKO mice and genes involved in lipid breakdown, including LPL and ATGL, were expressed at higher levels than those in control mice. This is consistent with mice, which bear an adipocyte-specific deletion of JAK2 leading to GH resistance; there is increased body fat and decreased lipolysis [20]. This mouse model, however, had no changes in energy intake or expenditure and inguinal adiposity predominated.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies, which demonstrate GH stimulation of lipolysis as well as a decrease in fatty acid synthesis have been performed in both rodents and humans [6-12]. In addition, transgenic animal models in which GH production or action have been altered provide further insight into the complexity of metabolic targets for GH [13-20]. Therefore, a physiologic mechanism(s) by which GH can either limit fat deposition and/or reverse obesity still requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Liver-specific deletion of GHR in mice results in a marked decrease in serum IGF-1 levels, significant increases in fat mass and serum lipids, and severe hepatic steatosis associated with systemic insulin resistance (22). A similar metabolic phenotype is observed in mice with liver-specific disruption of the GHR mediators Janus kinase-2 (JAK2) (23) or STAT5 (24). GH treatment in mice reduced diet-induced hepatosteatosis (21,25), and overexpression of a GHR antagonist increased hepatic steatosis (26).…”
Section: Introductionmentioning
confidence: 59%
“…However, ablation of JAK2 both in liver and adipose tissue resulted in significant reductions in hepatic TG levels as compared with JAK2L mice (23), but was still ∼2.5-fold greater than controls. Ablation of CD36 in the JAK2L mice (DKO-JAK2/CD36) improved hepatic TG content (5) as compared with JAK2L, but was still ∼20-fold higher than control mice.…”
Section: Discussionmentioning
confidence: 90%